Is sex associated with adverse outcomes after percutaneous coronary intervention for CTO?. (1st August 2019) - Akodad, Mariama; Spaziano, Marco; Garcia-Alonso, Carlos J.; Louvard, Yves; Sanguineti, Francesca; Garot, Philippe; Hovasse, Thomas; Unterseeh, Thierry; Chevalier, Bernard; Lefèvre, Thierry; Benamer, Hakim
Abstract: Background: Conflicting results have been reported regarding sex differences in percutaneous coronary intervention (PCI), but their potential influence on clinical outcomes after chronic total coronary occlusion (CTO) PCI remains unknown. We aimed to identify sex-related differences in long-term clinical outcomes after CTO PCI. Methods and results: All consecutive patients undergoing CTO PCI between 2004 and 2012 were included in a prospective registry. Baseline, procedural characteristics and clinical outcomes were compared according to sex. Out of 1343 patients, 194 were female (14.4%). Women were older (68.5 ± 9.9 vs 62.3 ± 10.8 years, p  < 0.001), more frequently diabetic (33.5% vs 26.4%, p  = 0.026) and hypertensive (70.1% vs 57.4%, p  < 0, 001), whereas males were more frequently smokers (28.5% vs 15.5%, p  < 0.001). J-CTO score was similar between both sexes (1.59 ± 0.91 vs 1.51 ± 0.88). The procedural success rate was also similar in men and women (74.0% vs 77.3%, respectively). At 8 years' follow-up, successful CTO PCI was associated with reduced mortality in women (14.8% vs 36.2%, p  = 0.003) and men (18.5% vs 29.1%, p  < 0.001). In successful CTO PCI cases, no sex-related differences were observed in terms of major adverse cardiac events. Conclusions: Our study suggests an equal benefit of CTO interventions with a marked reduction in mortality after successful CTO PCI in women and men alike. Highlights: Successful chronic total occlusion intervention may be associated with better prognosis regardless of sex. Chronic total occlusion intervention should, therefore, be performed in women indicated. The impact of success in chronic total occlusion interventions in women, on prognosis, is significant.